EFEKTIVITAS PEMBELAJARAN PROBLEM BASED LEARNING DENGAN ZOOM MEETING DI SDN KEBRAON II - Hadi Prayitno, Sunyoto (Jurnal Pendidikan Dasar, 2021)
Abstract: Teachers and students need the right media and appropriate learning during the COVID-19 pandemic. The target of achieving learning outcomes is the goal. This goal requires students to have critical thinking skills. By applying the problem-based learning model and the right media as well as the zoom meeting application to make it easier for teachers and students in teaching and learning activities. This research to know the effectiveness of problem-based learning by applying zoom meeting in class V of SDN Kebraon II is a descriptive quantitative study. The subjects used were fifth-grade students of SDN Kebraon II. Data were obtained using 4 instruments, namely: learning management observation sheets and student activity observations, learning outcomes test questions, and student response questionnaire sheets. Then the data were analyzed descriptively according to the indicators of each aspect, namely learning management, student activities, and learning outcomes, as well as student responses. The research results on the observation aspect of learning management have a value of 3.64 which is included in the "good" category. The observation aspect of student activity has an average of 91.275% included in the "very active" category. In the aspect of learning outcomes, the percentage of classical completeness of 87.5% (21) is included in the "completed" category. In the aspect of student response, 79.17% agreed to be included in the "positive" category. From the four aspects that have been met, problem-based learning with zoom meetings in class V SDN Kebraon II is said to be effective Keyword : effectiveness, problem based learning, zoom meeting Abstrak : Guru maupun siswa membutuhkan media yang tepat dan pembelajaran yang sesuai pada masa pandemi covid-19. Target mencapai hasil belajar menjadi tujuannya. Tujuan tersebut menuntut siswa memiliki kemampuan berpikir kritis. Dengan menerapkan model pembelajaran problem based learning dan media yang tepat serta aplikasi zoom meeting agar mempermudah guru dan siswa dalam kegiatan belajar mengajar. Penelitian dengan tujuan untuk mengetahui keefektivan pembelajaran problem based learning dengan menerapkan zoom meeting di kelas V SDN Kebraon II ini, merupakan penelitian kuantitatif deskriptif. Subjek yang digunakan adalah siswa kelas V SD Kebraon II. Data diperoleh dengan menggunakan 4 instrumen yaitu: lembar pengamatan pengelolaan pembelajaran dan pengamatan aktivitas siswa, soal tes hasil belajar, serta lembar angket respon peserta didik. Kemudian data dianalisis secara deskriptif sesuai dengan indikator masing-masing aspek yakni pengelolaan pembelajaran, aktivitas siswa, dan hasil belajar, serta respon siswa. Hasil researt pada aspek observasi pengelolaan pembelajaran memiliki nilai 3,64 termasuk pada kategori “baik”. Aspek observasi aktivitas siswa memiliki rata-rata 91,275 % termasuk dalam kategori “sangat aktif”. Pada aspek hasil belajar memiliki presentase ketuntasan secara klasikal sebesar 87,5% (21) termasuk dalam kategori “tuntas”. Pada aspek respon siswa 79,17% setuju termasuk dalam kategori “positif”. Dari keempat aspek tersebut telah terpenuhi maka pembelajaran problem based learning dengan zoom meeting di kelas V SDN Kebraon II dikatakan efektif. . Kata Kunci: efektivitas, problem based learning, zoom meeting